Understanding Space Weather: Solar Cycles and Magnetic Rossby Waves - Márquez-Artavia, Xiomara (2019)
The objective of this investigation is to explore the relationship between slow and fast magnetic Rossby waves and certain observations of long-term solar activity (months, years, decades, …). This paper seeks to determine if the periods of these waves correspond to the values recorded for cycles such as the Rieger cycle and the Haly cycle, or otherwise to quasi-periodic outbursts and of flares and Coronal Mass Ejections. The study begins with a literature review and a summary of the results of a Ph.D. dissertation that completely solves the mathematical model analyzed; using the equations derived from this previous work, the periods of the waves are calculated and then compared to observations. The results of this comparison suggest that certain types of solar activity may be due to Rossby magnetic waves originating within the Sun, specifically in the tachocline. The slow magnetic Rossby waves are associated with long-term and very long-term cycles, while the fast magnetic Rossby waves are a plausible cause for cycles with periods of months or a few years. The study of magnetic Rossby waves and their properties will doubtlessly provide new insights into the origin and properties of the solar magnetic field.